A novel positive detection system of in vivo mutations in rpsL ( strA) transgenic mice - Gondo, Yoichi; Shioyama, Yoshiyuki; Nakao, Kazuki; Katsuki, Motoya (Mutation Research/Environmental Mutagenesis and Related Subjects, 1996)
To positively detect the in vivo mutations accumulated in different mouse organs, we have developed a transgenic mouse system. This transgenic mouse carried an Escherichia coli (E. coli) plasmid pML4 as a shuttle vector that consisted of a replication origin ( ori), the kanamycin-resistant gene ( Kan R ) and the rpsL +) gene ( strA S ) derived from E. coli. These E. coli elements were expected to be inert in the transgenic mouse system; thus, neutral mutations would be accumulated on the shuttle plasmid in the transgenic mice. The shuttle plasmid vector was recovered from the mouse genomic DNA and introduced into kanamycin-sensitive (Km S) and streptomycin-resistant (Sm R) E. coli cells by using electroporation. The original pML4 shuttle plasmid transformed the host E. coli to Km R and Sm S, since both the Kan R and rpsL genes exhibited dominant traits of Km R and Sm S, respectively. On the other hand, when the retrieved pML4 shuttle plasmid carried a mutated rpsL gene, it could be positively detected as both Km R and Sm R. Based on this principle, we were able to positively detect the in vivo mutations accumulated in the rpsL transgene of the shuttle vector pML4 integrated into the mouse genome. The total number of rescued shuttle plasmids were counted on the plates containing Km alone, while only mutants were detected on the plates containing both Km and Sm. We have so far established 22 independent transgenic mouse lines that carried up to approx. 750 copies of the shuttle plasmid pML4 in a haploid genome. By using high-copy-number transgenic mouse lines which carried 350 copies or more of the shuttle vector, we also developed a simple and proficient method for retrieving the shuttle plasmid from various tissues of the transgenic mice. The background mutant frequency was approx. 5 × 10 −5. In order to validate the applicability of the positive-detection transgenic system for the induced mutagenicity assay, methylnitrosourea (MNU) was administered to the transgenic mice, and an increase in the number of mutant frequencies was seen in all tested organs including spleen, liver and brain. The rpsL transgenic mouse system was therefore considered to provide a quick-and-easy risk assessment test for in vivo tissue-specific mutagenicity, using positive detection by streptomycin.